A Happiness-Based View of the Firm - Pillania, Rajesh K. (Indian Journal of Marketing, 2024)
Purpose : There are many dangers, difficulties, and failures in the rapidly evolving business environment, which makes it imperative for companies to find innovative ways to conduct business. Design/Methodology/Approach : This conceptual and perspective paper used a primarily deductive approach and some inductive approach. Findings : Companies may confront new risks and difficulties and take advantage of opportunities by adopting a happiness-based vision of the company. A strategy based on happiness generates a long-term competitive advantage and has a favorable impact on the overall performance of the company as well as several functional areas. This viewpoint combines company and individual objectives. Sustainability follows happiness. A firm with a happiness-based perspective fosters success, sustainability, and happiness as mutually reinforcing objectives that benefit the individual, the business, the environment, and society as a whole. Practical Implications : This work has implications for governments, civil society, practitioners, and academicians. For governments, it created a new way to look at government policy to encourage a happiness-based view and create a win-win for individuals, firms, the environment, and society overall. It provided environmentalists and members of civil society with a fresh avenue for advocating for the preservation of the environment. Owners and professionals could view the company in a different light, and practitioners could address issues with business and strategy failure. It also provided researchers with an additional topic to explore. Originality/Value : This work suggested a new way to view a firm which created value for governments, civil society, business professionals, and academicians.